2021
DOI: 10.3389/fimmu.2021.728190
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cell Therapy: Hope for Patients With Systemic Lupus Erythematosus

Abstract: Systemic lupus erythematosus (SLE) is a chronic autoimmune disease. Although previous studies have demonstrated that SLE is related to the imbalance of cells in the immune system, including B cells, T cells, and dendritic cells, etc., the mechanisms underlying SLE pathogenesis remain unclear. Therefore, effective and low side-effect therapies for SLE are lacking. Recently, mesenchymal stem cell (MSC) therapy for autoimmune diseases, particularly SLE, has gained increasing attention. This therapy can improve th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 131 publications
1
38
0
4
Order By: Relevance
“…In the last two decades, there has been considerable data accumulated on applications of MSC for various autoimmune diseases. This is through the pioneering work mostly by the investigators of Far East and Middle East in single center-based trials at various academic institutions ( 64 , 71 73 ). The major rheumatological illnesses studied, so far, include SLE, SSC, and Rheumatoid Arthritis (RA).…”
Section: Msc Treatment Of Autoimmune Diseases—overview Of Publish Datamentioning
confidence: 99%
See 1 more Smart Citation
“…In the last two decades, there has been considerable data accumulated on applications of MSC for various autoimmune diseases. This is through the pioneering work mostly by the investigators of Far East and Middle East in single center-based trials at various academic institutions ( 64 , 71 73 ). The major rheumatological illnesses studied, so far, include SLE, SSC, and Rheumatoid Arthritis (RA).…”
Section: Msc Treatment Of Autoimmune Diseases—overview Of Publish Datamentioning
confidence: 99%
“…Laboratory parameters showed significant improvement in proteinuria and cytopenia, serum albumin and complement levels. Initial reports included decreased titers of double stranded DNA antibody, as well as increased blood T-regulatory (Treg) cells (CD4 + CD25 + Foxp3 +)—and decreased Th17- populations in the peripheral blood samples ( 73 , 78 ). A follow-up case report on two lupus patients treated with autologous MSC also had increased Treg cells, but the clinical improvement was marginal ( 79 ).…”
Section: Msc Treatment Of Autoimmune Diseases—overview Of Publish Datamentioning
confidence: 99%
“…Systemic lupus erythematosus (SLE) is a typical autoimmune disease characterized by excessive activation of T and B cells, producing a large number of autoantibodies and pro-inflammatory cytokines that result in tissue and organ damage ( 1 ). At present, there are few clinically approved traditional therapeutic drugs and biologic therapies for SLE ( 2 , 3 ). Animal models have made great contributions to the study of SLE pathogenesis and the development of new drugs.…”
Section: Introductionmentioning
confidence: 99%
“…The MSCs also display a wide range of immunomodulatory properties (21). MSCs transplantation (MSCT) displayed therapeutic effects on various autoimmune diseases, including systemic lupus erythematosus (22,23), SS (24), and rheumatoid arthritis (25,26). Our previous study showed that allogeneic MSCs prevented and suppressed SS-like symptoms in non-obese diabetic (NOD) mice (27).…”
Section: Introductionmentioning
confidence: 99%